Structurally Stable, High-Strength Graphene Oxide/Carbon Nanotube/Epoxy Resin Aerogels as Three-Dimensional Skeletal Precursors for Wave-Absorbing Materials - Lina Zhang; Guojun Song; Zetian Zhao; Lichun Ma; Hui Xu; Guanglei Wu; Yinghu Song; Yinuo Liu; Lihan Qiu; Xiaoru Li (Gels, 2022)
Three-dimensional (3D) graphene oxide aerogel (GOA) is one of the best fillers for composites for microwave absorption. However, its further development has been hindered by the poor mechanical properties. Methodology to improve the mechanical properties of the aerogel remains an urgent challenge. Herein, graphene oxide/carbon nanotube/epoxy resin composite aerogel (GCEA) was successfully prepared by a facile method. The results showed that the prepared GCEA with the hierarchical and 3D cross-linked structures exhibited excellent compression performance, structural and thermal stability, high hydrophilicity, and microwave absorption. The prepared GCEA recovered from multiple large strain cycles without significant permanent deformation. The minimum reflection loss (RL) was −39.60 dB and the maximum effective absorption bandwidth (EAB) was 2.48 GHz. The development of the enhanced GO aerogels will offer a new approach to the preparation of 3D microwave-absorbing skeletal materials with good mechanical properties.